2014
DOI: 10.1016/j.aller.2012.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between nasal eosinophils and nasal airflows in children with asthma and/or rhinitis monosensitised to house dust mites

Abstract: In this study, a close relationship was demonstrated between eosinophil infiltration and nasal airflows in children having asthma and/or rhinitis monosensitised to mites. Additionally, the significant association found between FEV1 values and nasal eosinophils or PNIFs supported the close link of upper and lower airways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
0
6
0
2
Order By: Relevance
“…A 2012 study of 37 pediatric patients with AR by Yukselen et al found a significantly higher nasal eosinophil count in patients with AR and coexisting asthma compared to patients with AR alone. 11 Canbaz et al, in a study of 37 patients with persistent AR, found a lower nasal airflow and a higher nasal eosinophil count in those with coexistent bronchial hyper-responsiveness. 19 According to the article, a cutoff point of 68% nasal eosinophils yielded a sensitivity of 100% (63.1 to 100) and a specificity of 58.6% (38.9 to 76.5) to determine the presence of bronchial hyper-responsiveness.…”
Section: Discussionmentioning
confidence: 92%
“…A 2012 study of 37 pediatric patients with AR by Yukselen et al found a significantly higher nasal eosinophil count in patients with AR and coexisting asthma compared to patients with AR alone. 11 Canbaz et al, in a study of 37 patients with persistent AR, found a lower nasal airflow and a higher nasal eosinophil count in those with coexistent bronchial hyper-responsiveness. 19 According to the article, a cutoff point of 68% nasal eosinophils yielded a sensitivity of 100% (63.1 to 100) and a specificity of 58.6% (38.9 to 76.5) to determine the presence of bronchial hyper-responsiveness.…”
Section: Discussionmentioning
confidence: 92%
“…Although this fact is expected, there are some contradictions in the available publications about the significance of TNAF in children with BA. So, Yukselen et al [ 20 ] observed the average degree of nasal obstruction in children with asthma with TNAF = 328±177 cm 3 /s. It should be noted that the causes of nasal obstruction were not elucidated in their study and the children's age was from 6 to 15 years.…”
Section: Discussionmentioning
confidence: 99%
“…Motomura et al [ 19 ] demonstrated that, for patients with asthma, a decrease in nasal airflow is characteristic, but the effect of the comorbid UAP on the respiratory function of the nose was not considered. Yukselen A. et al [ 20 ] established a significant relationship between spirometric parameters and nasal airflow in children with asthma. However, the effect of NOD on the respiratory function of the nose in this study was also not taken into account [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Um die Dringlichkeit der Maßnahme abzuschätzen und die Effizienz des diagnostischen Vorgehens zu erhöhen kann vor weiterführender Lungenfunktionsdiagnostik ein Asthmafragebogen ausgefüllt werden [23]. Alternativ kann die Notwendigkeit der Lungenfunktionsdiagnostik auch anhand des Peak Nasal Inspiratory Flow (PNIF) abgeschätzt werden, da dieser mit der Einsekundenkapazität (FEV1) bei Patienten mit einer Rhinitis korreliert [60].…”
Section: Lungenuntersuchungunclassified